Evaluating the Teaching of English for Civics: a Socio-Semiotic Perspective - Rika Jazilatul Kholidah, Neneng; Heru Woro Prastiwi, Chyntia; Fuadul Matin, Mohammad; Ismaya, Heru (KnE Social Sciences, 2022)
The development of four language skills relevant to Pancasila and Civics should be the focus of English instruction for civics in higher education in Indonesia. Students should be exposed to civics-related material in English for Civics programs, and they should be given opportunities to use that information in their daily life to hone their English language and literacy abilities. It must give students of English a simple approach to learning about Pancasila, Indonesian history, politics, citizenship, geography, and culture. Students who participate in civic education develop the attitudes and abilities required for democracy, such as a feeling of civic responsibility, critical thinking, and agency. Unfortunately, because listening skills were neglected, pupils often have uneven skills. According to the questionnaire results, students wish to participate in English language learning activities that involve public speaking, debating, writing, reading, and hearing in Pancasila and civics class. The researchers employed a sociosemiotic viewpoint to assess the existing syllabus, lesson plan, resources, teaching journal, mid-test questions, and final test questions to understand the changes that need to be made. To better suit the needs and objectives of the learners and to foster English proficiency, it will be highly helpful to revamp the English for Civics teaching and learning process. English proficiency must be associated with academic performance and plays a crucial role in training students to be knowledgeable and engaged. Keywords: English, Civics, Socio Semiotic Perspective, higher education